Uso da criptografia RSA no ensino de matemática - Rosa, Alex Almeida (2023)
We live in the age of technology, where information is passed on almost instantly by the means of communication. Messages are forwarded by the millions every hour. The objective of this work is to demonstrate how mathematics is important in this process, especially with regard to information security. We will explore the importance of fundamental mathematical concepts for understanding RSA Cryptography, which is the main theme of this work, such as Prime Numbers and Modular Arithmetic. Topics like this involving novelty and technology call the attention of students who during traditional classes generally do not combine theory and practice. For this reason, this work has as its final proposal the realization of a Didactic Sequence that associates theory with practice through free and easily accessible software and applications.